New anthraquinone and eurotinone analogue from the seeds of Senna obtusifolia and their inhibitory effects on human organic anion transporters 1 and 3. Issue 23 (2nd December 2019) - Pang, Xu; Wang, Li-Ming; Zhang, You-Cai; Kang, Li-Ping; Yu, He-Shui; Fan, Guan-Wei; Han, Li-Feng
Abstract: A continuous phytochemical study on the seeds of Senna obtusifolia (Syn.: Cassia obtusifolia ) led to the isolation of a new anthraquinone analogue, obtusifolin-2- O - β -D-(6'- O - α, β -unsaturated butyryl)-glucopyranoside (1 ) and a new eurotinone analogue, epi -9-dehydroxyeurotinone- β -D-glucopyranoside (2 ). Their structures were established mainly by NMR and MS experiments as well as the necessary chemical evidences. Their inhibitory effects on two organic anion transporters (OAT1 and OAT3) were investigated and the results showed that1 exhibited a strongly specific inhibitory effect on OAT1 at 100 μM. Abstract :